Stefan Parnicki-Pudełko w świetle dokumentów z Archiwum Uniwersytetu Wrocławskiego - Żmudziński, Mateusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
The Archives of the University of Wroclaw have preserved folders with documents related to the studies, the defense of the doctorate and the employment at the University of Wroclaw of S. Parnicki-Pudełko. They show the unconventional character and unusual career path of the young scientist. By the way, through these documents we get to know him as a committed patriot and social activist. Already at that time, his significant intellectual potential was noted, his enthusiasm for work and his excellent development was rightly predicted. Living in extremely difficult times, he knew how to maintain decency. In the later years of his life and career, he was associated with the Polish Academy of Sciences in Warsaw and then the Adam Mickiewicz University in Poznan where he spread his wings as a professor and head of the Novae archaeological expedition.